MXene-Coated Liquid Metal Nanodroplet Aggregates - Mason Zadan (8667870) (2025)
Combining droplets of liquid metal (LM) with nanomaterials often introduces synergistic thermal or electrical properties that are not found in the constituent materials alone. However, in these existing systems, LM droplets maintain a statistically uniform dispersion and are not capable of self-assembly or aggregation. These composites are limited by their need for high volume fractions of LM (>60 vol %) to achieve high thermal properties, introducing LM leaking as a drawback for thermal management and wearable electronic applications. In this work, we show that coating nanoscale droplets of eutectic gallium–indium (EGaIn) LM with small volume fractions of Ti3C2Tx MXenes (0.25 vol %) results in a unique LM morphology in which droplets self-assemble to form semisolid aggregates. This is accomplished by wrapping MXene sheets around individual LM droplets to create “sticky” particles that form self-assembled aggregates when mixed with a silicone oil. By introducing aggregation as a design parameter in soft LM composites, the thermal and electric resistance of the composite is shown to change dramatically. In contrast to silicone-based composites containing LM droplets or MXene nanosheets alone, these MXene-LM-silicone-based composites exhibit an exponential increase in thermal and electrical conductivity with decreasing interfacial thickness with significantly lower LM volume fractions (25 vol %) while avoiding LM rupture and bleed-out. This could enable more effective composites, reducing the amount of filler material required for thermal interface materials (TIM) and printed electronics.